Cognitive and Linguistic Manifestations of a Blind Child in Anthony Doerr’s All the Light We Cannot See - Md. Mozaffor Hossain (Bina Nusantara University, 2023)
The research intended to construe the interconnection among Marie-Laure’s blindness, thinking, and language and, thereby, explore if the language choice or spontaneous language of a blind person could be interpreted psycholinguistically in Anthony Doerr’s All the Lights We Cannot See. This novel presented the life-long stories of a girl and a boy whose paths merged eventually despite remaining unaffiliated throughout the first part of their life. Named Marie-Laure, the girl was blind and had her passage in her world through both sweet childhood experiences and chronologically upsetting predicaments. In the whole narrative of the novel, the novelist presented a reciprocal affiliation between Marie-Laure’s cognitive processing resulting from her physical condition, blindness, and language. Through portraying the predicaments of Marie-Laure, one of the two protagonists of All the Light We Cannot See, demonstrated vivid instances of the physical as well as mental trauma a blind child usually goes through. Concurrently, the novel also depicted conspicuously what improvisations a blind child had to devise to face reality, discern prevalent meanings of phenomena, construct her thoughts, and produce language. The research applied a qualitative method consisting of in-depth content analyses based on the selected text and secondary sources, namely published books, journals, and research articles. It analyzed the existing literature on the cognitive, psychological, and linguistic considerations of blind children and linked the discernment with the related portrayal in the narrative. The findings reveal substantial reciprocal dependence between a child’s physical authenticity and cognitive making, i.e., a child’s blindness influences his/her language, thoughts, and circadian psycholinguistic behavior.